Crystal Engineering of an nbo Topology Metal-Organic Framework for Chemical Fixation of CO2 under Ambient Conditions - Gao, Wen-Yang; Chen, Yao; Niu, Youhong; Williams, Kia; Cash, Lindsay; Perez, Pastor J.; Wojtas, Lukasz; Cai, Jianfeng; Chen, Yu-Sheng; Ma, Shengqian (Angewandte Chemie International Edition, 2014)
Crystal engineering of the nbo metal–organic framework (MOF) platform MOF‐505 with a custom‐designed azamacrocycle ligand (1,4,7,10‐tetrazazcyclododecane‐N,N′,N′′,N′′′‐tetra‐p‐methylbenzoic acid) leads to a high density of well‐oriented Lewis active sites within the cuboctahedral cage in MMCF‐2, [Cu2(Cu‐tactmb)(H2O)3(NO3)2]. This MOF demonstrates high catalytic activity for the chemical fixation of CO2 into cyclic carbonates at room temperature under 1 atm pressure. High catalytic activity for chemical fixation of CO2 into cyclic carbonates under ambient conditions has been demonstrated in the metal–organic framework (MOF) MMCF‐2 (see picture; C gray, O red, N blue, Cu pale blue). This MOF features a high density of well‐oriented Lewis acid active sites within the cuboctahedral cage.